Stability of the Syndesmosis After Posterior Malleolar Fracture Fixation. (January 2018) - Miller, Matthew A.; McDonald, Tyler C.; Graves, Matthew L.; Spitler, Clay A.; Russell, George V.; Jones, LaRita C.; Replogle, William; Wise, Jeremy A.; Hydrick, Josie; Bergin, Patrick F.
Background: We sought to define the rate of syndesmotic instability after anatomic reduction of the posterior malleolus when posterior stabilization of a trimalleolar or trimalleolar equivalent ankle fracture was chosen vs when a supine position and initially conservative management of the posterior elements was chosen. Methods: The types of syndesmotic and posterior malleolar fixation used to treat adult patients with ankle fractures involving the posterior malleolus at our level I trauma center were retrospectively assessed (N = 198). Specifically, both bimalleolar and trimalleolar fractures were included. Exclusion criteria included pilon fractures, trimalleolar fractures with Chaput fragments, and neurologic injury. Demographics, fracture classification, initial operative position, medial clear space, and posterior malleolar fragment size were recorded for each fracture. Results: In total, 151 patients (76.3%) were initially positioned supine, 27.2% of whom had syndesmotic instability requiring operative stabilization. Almost 25% of supine patients also underwent posterior malleolar stabilization for posterior instability. Overall, 73 (48.3%) patients who were initially treated in the supine position needed some form of additional stabilization. Forty-seven patients (23.7%) were initially positioned prone. Syndesmotic stability was restored in 97.9% of these patients. This 2.1% rate of instability vastly differs from the 13-fold higher syndesmotic instability rate observed in the supine group ( P < .001). Conclusion: Our data demonstrate that the rate of syndesmotic instability was reduced in trimalleolar and trimalleolar equivalent fractures when prone positioning and direct fixation of the posterior malleolus were first performed. Using traditional preoperative estimates of posterior stability to determine the need for posterior malleolar fixation may be inadequate since almost a quarter of patients treated supine received posterior stabilization. Level of Evidence: Level III, retrospective comparative series.